Effectiveness of Installment Payment Plan Program through Face-to-Face Service Channels and Non-Face-to-Face Service Channels - Bagaskara, Enggartyas; Fathiyah, Fenny (Jurnal Jaminan Kesehatan Nasional, 2024)
This study evaluates the effectiveness of registration services for BPJS Kesehatan's REHAB (Installment Payment Plan) program through face-to-face channels at branch offices and non-face-to-face channels via the Mobile JKN application. Employing a qualitative descriptive design, data were collected from 33 informants, including frontline coordinators, frontline staff, UP3KC staff, and 30 participants using purposive sampling. Data collection methods comprised interviews, observations, and documentation, with data validity ensured through triangulation. Analysis followed Miles, Huberman, and Saldana’s interactive model, involving data reduction, presentation, and conclusion verification. Results indicate that the Mobile JKN application is the preferred registration channel due to its convenience and practicality. At the same time, face-to-face services are utilized as a backup option during technical disruptions. However, challenges such as incorrect participant data and system reliability hinder registration. This study underscores the need for improvements in the Mobile JKN system, particularly in data validation and technical stability, to enhance service accessibility and ensure seamless participant registration